Two new species of Aphanarthrum Wollaston (Coleoptera: Curculionidae, Scolytinae) associated with Euphorbia in South Africa - Jordal, Bjarte H. (Zootaxa, 2009)
Two species of Aphanarthrum collected from dead spurges of Euphorbia in South Africa are illustrated and described as new to science. They represent the first records from the southern parts of Africa and thus significantly extend the known distribution of the genus. Analyses of the phylogenetic relationships of the species of Aphanarthrum and Coleobothrus based on molecular and morphological characters yielded a relatively well supported but nevertheless distant sister relationship between the two South African species. Their relationship to other Aphanarthrum remains uncertain and revealed deep divergence, indicative of a rather ancient origin. The peripheral distribution of the South African species and the broad availability of suitable host plants throughout the continent suggest that more species remain to be discovered in this region.